2013
DOI: 10.1002/ajhb.22462
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and obesogenic factors associated with inflammation in Chinese children, adolescents and adults

Abstract: Objectives Influenced by pathogen exposure and obesity, inflammation provides a critical biological pathway linking changing environments to the development of cardiometabolic disease. This study tests the relative contribution of obesogenic and pathogenic factors to moderate and acute CRP elevations in Chinese children, adolescents and adults. Methods Data come from 8795 participants in the China Health and Nutrition Study. Age-stratified multinomial logistic models were used to test the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
1
24
1
Order By: Relevance
“…Where infectious disease load is high and energetic resources limited, immune functioning may be prioritized over growth and/or malnutrition may predispose to infection. Yet as Thompson et al () have shown in China, such tradeoffs can be masked in populations undergoing a nutritional transition, even with large numbers living in persistent poverty. Worthman and Panter‐Brick (), in their work with Nepalese children, demonstrate another way that tradeoffs may fail to transfer in the expected ways from one population to another.…”
Section: Discussionmentioning
confidence: 99%
“…Where infectious disease load is high and energetic resources limited, immune functioning may be prioritized over growth and/or malnutrition may predispose to infection. Yet as Thompson et al () have shown in China, such tradeoffs can be masked in populations undergoing a nutritional transition, even with large numbers living in persistent poverty. Worthman and Panter‐Brick (), in their work with Nepalese children, demonstrate another way that tradeoffs may fail to transfer in the expected ways from one population to another.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals were considered to have NCD morbidity if they reported cardiovascular or other chronic disease symptoms. Individuals were considered to have infectious morbidity if they or their caretaker for children under 10 reported respiratory or gastrointestinal symptoms or had a C‐reactive protein levels >3 mg/L for children (Thompson, Houck, Adair, et al, ; Wander, Brindle, & O'Connor, ) and > 10 mg/L for adults (Pearson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Since biomarkers were collected in only a subset of individuals, we used the occurrence of one or more risk factors (Table ) to categorize individuals into four groups: no risk factors, UND/ID only, OWT/NCD only, or dual burden. Individuals were considered to have UND/ID if they reported infectious symptoms, were stunted, were underweight, had iron deficiency anemia, or had acutely elevated CRP (levels >3 mg/L for children [Thompson, Houck, Adair, et al, ; Wander, Brindle, & O'Connor, ], and > 10 mg/L for adults [Pearson et al, ]). Individuals were considered to have OWT/NCD if they had one or more of the following risk factors: reported NCD symptoms, moderately elevated CRP (1‐3 mg/L in children [Skinner, Steiner, Henderson, & Perrin, ; Thompson, Houck, Adair, et al, ] or 3‐10 mg/L in adults [Pearson et al, ]), were overweight or obese, had high waist‐to‐height ratio, mean systolic or diastolic blood pressure indicative of prehypertension or hypertension, or, for adults only, impaired glucose, high Homa‐IR, high total cholesterol, high LDL cholesterol, or low HDL cholesterol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While much remains unknown regarding the connection between human microbiomes and obesity (Harley and Karp, ; Walters et al, ), certain alterations in human gut microbiome profiles are associated with increased energy harvest capacity (Jumpertz et al, ; Rosenbaum et al, ). Gut microbiota also help to regulate inflammatory signaling pathways; systemic low‐grade inflammation is commonly associated with obesity and its related pathologies in mice and humans (Cani et al, ; Thompson et al, ).…”
Section: Introductionmentioning
confidence: 99%